The Global Regulator CcpA of Listeria monocytogenes Confers Sensitivity to Antimicrobial Fatty Acids - Thomasen, Rikke S. S.; Jespersen, Magnus Ganer; Jørgensen, Katrine; dos Santos, Patricia T.; Sternkopf Lillebæk, Eva M.; Skov, Marianne N.; Kemp, Michael; Kallipolitis, Birgitte H. (Frontiers in Microbiology, 2022)
Free fatty acids (FFAs) are known to exhibit antimicrobial and anti-virulent properties against bacterial pathogens. Specific FFAs, such as lauric acid (LA; C12:0), exert both effects against the foodborne pathogen Listeria monocytogenes: at low levels, LA acts to inhibit the activity of the virulence regulator PrfA, whereas at higher levels, LA inhibits bacterial growth. Deletion of prfA is known to promote tolerance towards antimicrobial FFAs, suggesting that the response of L. monocytogenes to anti-virulent and antimicrobial FFAs could be linked. In this study, we explored the response of L. monocytogenes towards antimicrobial FFAs holding an anti-virulence activity by isolating strains that can grow at high concentrations of LA. We found that LA-tolerant isolates carry mutations in the gene encoding the global regulator CcpA. Importantly, we discovered that mutation or deletion of ccpA protect L. monocytogenes against the antimicrobial activity of FFAs, whereas the ccpA mutants remain sensitive towards FFA’s PrfA-inhibitory effect. A regulatory link involving CcpA, connecting the response towards the antimicrobial and anti-virulence activities of FFAs, is therefore unlikely. To further study how deletion of ccpA promotes FFA tolerance, we performed a transcriptomic analysis of the response to LA. Our data indicated that the FFA-tolerant phenotype of ∆ccpA is not induced upon LA exposure but appears to be an inherent phenotypic trait of the ccpA deletion mutation. Interestingly, we found that the bacterial surface of L. monocytogenes becomes more hydrophilic upon deletion of ccpA, and we demonstrate that CcpA plays a role in the response of L. monocytogenes to other stress conditions, including low pH and antibiotics. Altogether, our study revealed that regulatory activities of CcpA lead to an increased hydrophobicity of the bacterial surface, which may confer sensitivity of L. monocytogenes against the antimicrobial activity of FFAs. Notably, CcpA is not involved in responding to the PrfA-inhibitory effect of FFAs, showing that FFA-tolerant strains can still be targeted by the anti-virulent activity of FFAs.